2001
DOI: 10.1159/000046709
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Factor Eating Questionnaire in the Evaluation of Eating Behaviour in Subjects Seeking Participation in a Dietotherapy Programme

Abstract: Aim: To evaluate the eating behaviour in normal-weight, overweight, and obese women seeking participation in a diet-based programme of weight reduction or achievement of ideal body weight. Methods: Thirty-seven obese, 42 overweight, and 14 normal-weight subjects, seen at an Italian university outpatient clinic, were asked to complete the Stunkard and Messick three-factor eating questionnaire (TFEQ). The TFEQ is designed to evaluate three different factors in eating behaviour: restraint, disinhibition, and hung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 20 publications
5
31
0
2
Order By: Relevance
“…22,28 Furthermore, a study by de Lauzon-Guillain et al 27 found that restrained eating was associated with adiposity (which included BMI measurements) in normal weight participants, but not in overweight participants. This finding was not refuted with respect to the direction of such a relationship in our studyFin the non-obese population, the association between BMI and CR was also positive (although not significant).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,28 Furthermore, a study by de Lauzon-Guillain et al 27 found that restrained eating was associated with adiposity (which included BMI measurements) in normal weight participants, but not in overweight participants. This finding was not refuted with respect to the direction of such a relationship in our studyFin the non-obese population, the association between BMI and CR was also positive (although not significant).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found a positive cross-sectional association between restrained eating and BMI, 19,20 whereas others found no significant relationships 6,21 or inverse relationships. 22,23 In this investigation, we examine the relationship between restrained eating and BMI using participants with a range of BMI, as well as clinical and non-clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, changes in subscales of TFEQ have been associated with changes in weight, energy intake and success or failure of WM. High restraint, low disinhibition and low hunger scores have been associated with a more balanced diet 17 and successful WM [18][19][20][21] in women. Similar results have been observed in men, although less often studied.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, successful restraint may not result in observed differences in food intake between groups of restrained and unrestrained eaters because appetitive traits vary by individual and are associated with susceptibility to weight gain, 36,37 and hence are unlikely to be evenly distributed Dietary restraint and self-regulation F Johnson et al between these groups. The cross-sectional association between restraint and body mass index (BMI) has been examined in several studies, and positive, 38,39 negative 40,41 and null associations between restraint and BMI have been reported. However, a consistent finding has been that associations between dietary restraint and body weight vary between obese and normal weight populations.…”
Section: Widely Used Methods Of Measuring Dietary Restraint Confound mentioning
confidence: 99%